How Did Bekasi City’s Local Government Navigate The Turbulence Using Accounting and Financial Management? - Hans Victor Sitepu (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
Despite facing significant turbulence from many internal challenges, the Bekasi municipal government is able to handle regional finances effectively to provide prosperity to all of its inhabitants. The purpose of this study was to investigate the numerous causal elements that have enabled Bekasi City to reach this famous reputation. This study using descriptive quantitative approach to analyze financial performance of Bekasi City. Six local government financial indicators are utilized to investigate this, including Fiscal Decentralization Ratio, Local Financial Independence Ratio, Capital Expenditure Activity Ratio, Operating Expenditure Activity Ratio, Effectiveness Ratio, and Growth Ratio. The six indicators are calculated using performance figures from the Bekasi City Regional Government Audited Financial Report from 2018 to 2023. The Fiscal Decentralization Ratio, Operating Expenditure Ratio, Capital Expenditure Ratio, and Growth Ratio all improved but remained in the same level from 2018 to 2023, whereas the Local Financial Independence Ratio and Effectiveness Ratio improved over the last four years. This study contributes empirical insights to demonstrate how public sector’s financial management can be utilized by municipal government to face challenging times. The researcher anticipates that additional research will help to better understand the empirical reasons of the numerous financial performance occurrences identified in this study.